Suicide and socioeconomic determinants in Canada: beyond morality and philosophy - Lau, Evan; Siti Nur Zahara, Hamzah; Chia, Sandra Chia Tan; Biagio, Simonetti (Springer Science+Business Media Dordrecht, 2017)
This paper provides new and exciting insight of suicide between genders in Canada for 39 years from a socio-economic perspective. A theoretical framework based on sound economic theory of suicide using Vector Autoregression (VAR) model to establish meaningful relationships between variables incorporated. Additional causality test and beyond sample analysis (forecasting) will be helpful inbeautifying the linkages among the variables employed in this study. It is suggested that both female and male suicidal behaviour can be explained by socio-economic indicators. The findings provide useful insights for policy makers and suicide related agencies to perform a novel approach in dealing with suicides in addition to traditional behavioural correction and counselling strategies in hand. This study should also be helpful in understanding suicide from a broad perspective and analysing suicide in a new economic framework of rational choice theory.